Global Awareness In Paula Meehan's Work: The Intersection of Local and Global Consciousness in Paula Meehan's Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In "The Future of IrishPoetry?" Richard Tillinghast claims that the new generation of Irishpoets—in contrast to the previous one dominated by figures such as Yeats, Mac Neice,Kavanagh, and Heaney—has a weaker sense of local rootedness, place, andlocality. Whereas these previous writers shared a strong concern with ideas ofnationhood and locality, [w]hen we come to the new poets . . . that old senseof Ireland seems to have gone up in smoke. It would seem that now, as aprosperous member of the European Union, host to waves of emigration fromEastern Europe and elsewhere, Ireland is just like everywhere else. In contrast to Tillinghast'sview, Meehan's work, from earliest to her most recent, shows how the localcontinues to be central to her aesthetic. This sense of rootedness in Irelandis nonetheless combined with an awareness of oppression in other parts of theworld, an awareness which was perhaps absent in the work of those poets thatTillinghast considers literary precedents of recent Irish writers. As thiscritic points out in reference to Harry Clifton, contemporary Irish poetry"shows how much the world has changed, how glaringly its inequalities,brutality and exploitation impress themselves on" writers who are able toput themselves "in a position to see first-hand what is happening in otherparts of the world—other cultures that MacNiece, Heaney and Kavanagh would seemto have had little interest in" (170). This article shows how Meehan'swork is driven by the "globalist" impulse of creating anopentranslocal solidarity among oppressed communities. Her stance could besummarized as what globalization theorist Gilroy calls a "metropolitanplanetary consciousness" (83), an attempt to connect, on a global scale,disparate minorities by seeking resemblances between one another. While priorwork has explored.